THE IMPACT OF CONVERSION OF AGRICULTURAL LAND ON FARMERS' INCOME IN SLEMAN DISTRICT - Anggraeni, Rini; Kadarso, Kadarso; Arumndalu, Hanna Syahrina (Agros Journal of Agriculture Science, 2024)
This research was carried out with the aim of knowing: (1) the impact of the transfer of agricultural land functions on the income of farmers in the Sleman District. and (2) the effect of transfer of the functions of farmland on the value of the production of rice that is lost in the Sleman District. The basic method used in this research is the method of quantitative descriptive analysis. The location of the study is determined by non-probability sampling. The non-probability sampling method is Snowball Sampling. with 15 people moving land and 15 people not moving land. The results of the research showed that: (1) Significant income difference to the impact of the presence of agricultural land function. Farmers income before the land function has an average income of Rp.581.212/UT. or Rp.11.779.477/Ha and after the existence of overload of land function of Rp.4.663.149/UT or Rp.48.190.505/Ha with a difference in income of Rp.4.081.937/year or Rp.340.161/month. (2) The value of grain production that is lost each year increases as a result of the transfer of land functions of Rp.7.509.637.270,00/Kg.Keywords: transfer of agricultural land functions, farmers’ income, rice plantINTISARIPenelitian ini dilakukan dengan tujuan untuk mengetahui: (1) dampak alih fungsi lahan pertanian terhadap pendapatan petani di Kabupaten Sleman. dan (2) dampak alih fungsi lahan pertanian terhadap nilai produksi padi sawah yang hilang di Kabupaten Sleman. Metode dasar yang digunakan dalam penelitian ini adalah metode analisis desktiptif kuantitatif. Lokasi penelitian ditentukan dengan metode sampling non-probability. Penentuan responden menggunakan metode nonprobability sampling yaitu Snowball Sampling dengan jumlah responden 15 orang mengalihkan lahan dan 15 orang tidak mengalihkan lahan. Hasil penelitian menunjukan bahwa: (1) Perbedaan pendapatan yang signifikan terhadap dampak adanya alih fungsi lahan pertanian. Pendapatan petani sebelum alih fungsi lahan memiliki pendapatan rata-rata sebesar Rp.581.212/UT atau Rp. 11.779.477/Ha dan setelah adanya alih fungsi lahan sebesar Rp.4.663.149/UT atau sebesar Rp.48.190.505/Ha dengan selisih pendapatan sebesar Rp.4.081.937/Tahun atau sebesar Rp.340.161/Bulan. (2) Nilai produksi padi yang hilang setiap tahun mengalami peningkatan akibat adanya alih fungsi lahan sebesar Rp.7.509.637.270,00/Kg.Kata Kunci: Alih Fungsi Lahan Pertanian, Pendapatan Petani, Padi